The use of minimal surface principles and multiplex joinery system for designing post-disaster construction systems - Stephanus Evert Indrawan; Gervasius Herry Purwoko; Tri Noviyanto P. Utomo (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2020)
Indonesia is located in a geographic area that is prone to disasters; thus, it is necessary to raise awareness about the science of disaster mitigation, including the provision of safe/suitable temporary shelter/building facilities for victims. In a number of disasters, it can be seen that confusion and access to the affected transportation will lead to difficulties in delivering disaster relief and supporting equipment to build post-disaster facilities. Therefore, we need a construction system that is easily assembled, stable, and easy to carry. In this case, the designer uses one type of shell structure, i.e. Minimum Surface principle which is the basis of the Inflatable Structure or Pneumatic Structure. By developing lightweight structures that refer to this principle, the designer can process architectural forms that are lighter and more stable. In this paper, the discussion is limited to the use of materials made from plywood based on the principle of Minimal Surface structure because this material is easily obtained and processed. The research questions of this study are how to create a fast raft construction system for post-disaster needs with plywood base material and how to process the connection system or plywood construction to have structural capability. © 2020 Stephanus Evert Indrawan, Gervasius Herry Purwoko, Tri Noviyanto P. Utomo